A prospective cohort study on symptoms of common mental disorders among Dutch elite athletes - Gouttebarge, V.; Jonkers, R.; Moen, M.; Verhagen, E.; Wylleman, P.; Kerkhoffs, G. (The Physician and Sportsmedicine, 2017)
Objective: Scientific knowledge about symptoms of common mental disorders in elite sports is scarce. Consequently, the objectives of the study were to (i) establish the 12-month incidence of symptoms of common mental disorders (CMD; distress, anxiety/depression, sleep disturbance, adverse alcohol use, eating disorders) among Dutch elite athletes and (ii) explore their potential association with several stressors (being injured, recent life events, career dissatisfaction).